Antibacterial activity of freshwater lobster (Cherax quadricarinatus) shell chitosan gel preparation against Escherichia coli and Staphylococcus aureus - Zulmai Rani, Ridwanto, Haris Munandar Nasution, Vera Estefania Kaban, Nasri Nasri, Nurhayati Br Karo (Journal of Applied Pharmaceutical Science, 2023)
Chitosan is a modified carbohydrate polymer obtained from the deacetylation of chitin and has good and unique characteristics, including its ability to be biodegradable, biocompatible, and non-toxic. The purpose of this study was to manufacture chitosan from freshwater lobster shells formulated in the form of a hand sanitizer gel that is stable and determine its antibacterial activity against Escherichia coli and Staphylococcus aureus. The chitosan obtained was then made into hand sanitizer gel preparations with concentrations of 1.5%, 3%, and 4.5%, and then an evaluation test was carried out on the hand sanitizer gel preparation, as well as antibacterial testing against E. coli and S. aureus. The results showed that the hand sanitizer preparation in the organoleptic test did not show any change in odor, shape, and color. The homogeneity test showed the absence of coarse granules. The results of the pH testing confirmed that the pH of the preparation was still within the permitted criteria limits. The dispersion test also showed the average is in the range of 5–7 cm so that the formula meets the requirements. The results of the antibacterial activity test of the chitosan hand sanitizer gel showed that it can inhibit E. coli bacteria with the best inhibition zone obtained at a concentration of 4.5% at 8.8 mm and S. aureus with the best inhibition zone at 10 mm.
Keywords: Freshwater lobster, chitosan, gel hand sanitizer, Escherichia coli, Staphylococcus aureus